Significance of social vision in the process of reshaping islamic education - Rahath House, Yousef (IIUM Press, 2015)
The purpose of this paper is to discuss the importance of social vision of Islam in formulating Islamic education. It has been assumed that due to neglecting the social dimension of Islam, most of the contemporary Islamic educational institutions are incapable of enabling the younger generation to look at the historical context of their lived reality more critically. Consequently, most of the Muslims are not bothered about several concrete human social problems such as inequality, economic exploitation and fragmentation of the community into different classes and groups. To solve this issue, the article suggests incorporation of the social dimension of Islam in the educational curricula. Since the Quran portrays human being as a social being by highlighting his various responsibilities in this world, one of the guiding principles of Islamic education should be to make Muslims capable of understanding the world for making it more just and better. Only then would Muslims be able to make a link between knowledge and action.